CALCULATION OF PIT 2 PRODUCED OVERBURDEN VOLUME AND THE ANALYSIS OF PREPARATION OF PIT 1 MINE VOID UTILIZATION AT SUPAT BLOCK PT. BATURONA ADIMULYA MUSI BANYUASIN, SOUTH SUMATERA - Edwin Harsiga; Taufik Toha; Syamsul Komar (Research Centre of Inorganic Materials and Complexs, 2018)
PT BaturonaAdimulya is a coal mining company located in BabatSupatSubdistrict, MusiBanyuasin Regency, South Sumatera Province. Based on the calculation of overburden digging volume at Pit 2 with progress survey that is measurement using total station sokkia set 3010 instrument and the processing and calculation using surpac 6.5.1 result in overburden volume or cover ground 251,941 BCM. Coal mining in open pit will cause environmental changes, either small hills or mined holes (voids). The burden removing from Pit 2 by backfilling method in the mining area will minimize the voids that occur. PT BaturonaAdimulya has void in Pit 1 as large as 4.8 Ha, and will do backfilling that requires overburden material as much as 295.721 BCM / Ha and top soil as much as 33,600 LCM / Ha. The voids left at the end of the mine without any utilization planning have the potential to cause undesirable impacts on the environment. Therefore, PT BaturonaAdimulya is planning to revegetate the void area so it can be utilized and become a green field again as before